Representation of Father and Son Relationship in Film Mencuri Raden Saleh (Roland Barthes' Semiotic Analysis) - Nurrochman, Habib; Wirawanda, Yudha (Universitas Muhammadiyah Surakarta, 2023)
The film Mencuri Raden Saleh, one of Angga Dwimas Sasongko's works, is one of the first films in Indonesia to introduce the concept of the heist genre. This film tells the story of a group of students who initially did not intend to steal a historical painting, namely the Arrest of Prince Di Ponogoro. The formulation of the problem in this study is: How is the Representation of Father and Son Relationship in the Film Mencuri Raden Saleh? With the aim to be achieved in this study to find out the representation of the relationship between father and son in the film. This research uses a qualitative analysis approach using Roland Barthes' semiotic theory. Data collection in this study came from 2 sources, namely primary data and secondary data. Primary data mapping serves to obtain the source of the film Mencuri Raden Shaleh obtained from a streaming application (Netflix), then for secondary data this research uses supporting reading sources such as journals, news, books or readings whose case studies are still related to the film. The validity of the data used is the source triangulation technique. The results of this study obtained a pattern of loving relationships between the closeness of a father to a child and also a child to a father, which shows a sense of care, care, and affection, even though some of them are facing problems.